The Edward James Collection : Dali, Magritte and other Surrealists. - Scottish National Gallery of Modern Art, Edinburgh (Edinburgh : Scottish National Gallery of Modern Art, 1976)
de Chirico, Giorgio ; Dali, Salvador ; Delvaux, Paul ; Ernst, Max ; Magritte, René ; Tchelitchew, Pavel
The Edward James Collection : Dali, Magritte and other Surrealists, Scottish National Gallery of Modern Art, Edinburgh, 12 August - 12 September 1976
boek